2017
DOI: 10.18632/oncotarget.17856
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cervical cancer recurrence using textural features extracted from 18F-FDG PET images acquired with different scanners

Abstract: ObjectivesTo identify an imaging signature predicting local recurrence for locally advanced cervical cancer (LACC) treated by chemoradiation and brachytherapy from baseline 18F-FDG PET images, and to evaluate the possibility of gathering images from two different PET scanners in a radiomic study.Methods118 patients were included retrospectively. Two groups (G1, G2) were defined according to the PET scanner used for image acquisition. Eleven radiomic features were extracted from delineated cervical tumors to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 44 publications
2
70
0
3
Order By: Relevance
“…A first study associated high pretreatment PET GLNU GLRLM with poorer prognosis [9]. Another showed that 18 F-FDG PET/CT features could predict local recurrence of LACC better than SUV max [13]. A third study showed that DCE-MRI 2 nd -order textures could predict treatment outcome [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first study associated high pretreatment PET GLNU GLRLM with poorer prognosis [9]. Another showed that 18 F-FDG PET/CT features could predict local recurrence of LACC better than SUV max [13]. A third study showed that DCE-MRI 2 nd -order textures could predict treatment outcome [10].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in addition to conventional parameters on FDG PET/CT and MRI used to stage disease, plan treatment and assess response there has been a growing interest in the extraction of quantitative features from medical images, denoted radiomics [6]. Radiomics features are statistical or model-based metrics to quantify tumor intensity, shape and heterogeneity which have been shown to reflect intratumoral histopathological properties [7] and to provide prognostic information in several pathologies [8] including CC [9][10][11][12][13]. Radiomics on pretreatment PET/CT has been shown to predict response to therapy and risk of pelvic recurrence in CC [9,11,13] and used to characterize CC lesions from diffusion-weighted MRI (DW-MRI) [12] or dynamic contrast enhancement MRI (DCE-MRI) [10].…”
Section: Introductionmentioning
confidence: 99%
“…15 In cervical cancer for example, a small subset of PET/CT radiomic features has been found to be of greater value than the SUV max or standard clinical variables to predict local recurrence. 32,37 The case of neoadjuvant treatments (e.g. radiochemotherapy) represents an interesting challenge for prediction modelling, as the definitive answer is provided by histological analysis.…”
Section: Radiomics As a Prognostic And Predictive Indicatormentioning
confidence: 99%
“…Hierbei wurde auch gezeigt, dass die Wahl der Raster-bzw. der Voxelgröße, siehe [7,16,21] und [25], durchaus einen sehr großen Einfluss auf die Analyse hat.…”
Section: Segmentierungunclassified